Calorimetric study of the superconducting and normal state properties of Ca(Fe1−xCox)2As2 - Singh, Surjeet (IOP Science, 2012)
We present a calorimetric study on single crystals of Ca(Fe1−xCox)2As2 (x = 0, 0.032, 0.051, 0.056, 0.063, and 0.146). The combined first order spin-density wave/structural transition occurs in the parent CaFe2As2 compound at 168 K and gradually shifts to lower temperature for low doping levels (x = 0.032 and x = 0.051). It is completely suppressed upon higher doping x ≥ 0.056. Simultaneously, superconductivity appears at lower temperature with a transition temperature around Tc ~ 14.1 K for Ca(Fe0.937Co0.063)2As2. The phase diagram of Ca(Fe0.937Co0.063)2As2 has been derived and the upper critical field is found to be μ0H(c)2 = 11.5 T and μ0H(ab)c2 = 19.4 T for the c and ab directions, respectively.
Only IISERM authors are available in the record.
Keywords: Calorimetric study; Single crystals; Lower temperature; Phase diagram